2011
DOI: 10.20996/1819-6446-2011-7-2-137-144
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Cardiovascular Risk Factors Prevalence and Efficacy of Their Correction in Physicians. Estimation of Physicians’ Expertise in Up-to-Date Clinical Guidelines. Results of the “Physician’s Health and Education” Study

Abstract: Дроздова Любовь Юрьевна-м.н.с. отдела профилактической фармакотерапии ГНИЦ ПМ Марцевич Сергей Юрьевич-д.м.н., профессор, руководитель того же отдела; профессор кафедры доказательной медицины Первого МГМУ им. И.М. Сеченова Воронина Виктория Петровна-к.м.н., с.н.с. того же отдела Studies aiming at evaluation of general practitioners' health have become popular during the last two decades. First large-scale trials in this area studied the role of biochemical markers and possibilities of aspirin and vitamin E ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 9 publications
0
2
0
2
Order By: Relevance
“…Clinical guidelines in Russia are very similar to Europe as they are translated and adapted from the guidelines of the European Society of Cardiology. The state of knowledge concerning the efficacy of statins in the Russian medical profession is underlined by a recent study of physician health in Russia which found that physicians themselves do not take statins even if they are at very high risk of cardiovascular disease (only 13 % of physicians who needed statin treatment actually took it) [ 37 ]. If physicians themselves do not think it is necessary to take statins themselves this decreases the chance of systematic prescription of statins to patients.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical guidelines in Russia are very similar to Europe as they are translated and adapted from the guidelines of the European Society of Cardiology. The state of knowledge concerning the efficacy of statins in the Russian medical profession is underlined by a recent study of physician health in Russia which found that physicians themselves do not take statins even if they are at very high risk of cardiovascular disease (only 13 % of physicians who needed statin treatment actually took it) [ 37 ]. If physicians themselves do not think it is necessary to take statins themselves this decreases the chance of systematic prescription of statins to patients.…”
Section: Discussionmentioning
confidence: 99%
“…A further potentially strong influence on patient adherence and persistence is the personal beliefs of health professionals and general population attitudes. ‘Therapeutic inertia’ among physicians has been reported to contribute to poor management of cardiovascular risk factors in Russia and the USA [24, 25]. The fact that 31% of the post-MI subgroup of DIAPAsOn were classified as current smokers may be indicative of attitudinal factors that operate to the general detriment of adherence.…”
Section: Discussionmentioning
confidence: 99%
“…По данным Л.Ю. Дроздовой и соавт., которые были опубликованы в 2011 г., 59% врачей не посчитали нужным немедленно назначить лекарственную терапию пациенту с АГ и высоким риском ССО [8]. Анализ ответов на вопросы первого раздела основной части анкеты позволяет прийти к заключению о том, что врачи не придают должного значения стратификации риска ССО у пациентов с АГ и недооценивают значение этого этапа диагностики для правильного выбора антигипертензивной терапии.…”
Section: Discussionunclassified